Development of a Reference Handbook Based on Contextual Teaching Learning in Curriculum Studies Course - Beta Wulan Febriana; Widinda Normalia Arlianty (Universitas Islam Indonesia, 2018)
ABSTRACT: The study aims to find out the implementation of reference handbook based on CTL. Design of the study is a modified Research and Development (R&D) developed by Borg and Gall. Subjects in this study are students of Chemical Education Major in Islamic University of Indonesia in the odd semester of academic year 2016/2017. The reference handbook arranged has been validated by academics and practitioners and categorized as